An analysis of the impact of corporate governance on the financial performance of state enterprises and parastatals: a case of Air Zimbabwe - Ncube, Nothando (2018)
This research is an investigation of the relationship between corporate governance and financial performance at Air Zimbabwe. The objectives of this research were to investigate the extent to which Air Zimbabwe has been implementing corporate governance principles and whether a relationship exists between corporate governance and financial performance. Literature reviewed corporate governance fundamental theories such as agency, resource dependency and stewardship to portray how corporate governance can impact financial performance. The researcher used primary data collected through structured questionnaires with closed ended questions. They were conducted using principles articulated by the Organization for Economic Cooperation and Development (OECD). The information obtained were analyzed using statistical tool of analysis including, percentage, frequencies, mean, standard deviations and statistical package for social sciences for regression analysis. To measure financial performance an accounting based performance measure Return on asset (ROA) was used. Multiple regression was also used to measure the extent to which corporate governance influence financial performance and the results were that corporate governance variables like independence of the audit committee, board’s ownership, CEO duality, board’s independence positively influence financial performance while board size negatively influence financial performance. The recommendations were that Air Zimbabwe should incentivize programs meant to foster and implement corporate governance and to effectively adopt IPSAS (International Public-Sector Standards) so as to advance financial reporting.